Decomposition from legume and non-legume crop residues: effects on soil organic carbon fractions under controlled conditions - De Sa Pereira, Eduardo; Duval, Matias Ezequiel; Galantini, Juan Alberto (Sociedad Española de la Ciencia del Suelo, 2019)
Cover crop (CC) residues protect the soil from erosion and their permanence on the surface is largely influenced by their biochemical constituents. We performed a study under controlled conditions to investigate the dynamics of legume and non-legume CC residues decomposition and the transformations of the soil labile organic carbon fractions in the surface layer (0-15 cm). The experiment was carried out on a Typic Argiudoll (clay loam, 27.4 g kg-1 soil organic matter, 14 mg kg-1 extractable phosphorus and 6.5 pH) placed in undisturbed pots (1570 cm3) in a greenhouse under controlled conditions of temperature (25 ± 1 °C). We evaluated three CC species (oat, Avena sativa L.; vetch, Vicia sativa L.; Persian clover, Trifolium resupinatum L.) and a no-CC control (fallow). Shoot residues were applied on the soil surface at 5.4, 5.4 and 2.7 g dry matter (equivalent to 6, 6 and 3 Mg ha-1 for oat, vetch and clover, respectively) and incubated for 362-days (eight sampling times). The water content in the pots was maintained periodically by weight at 60% of soil water-holding capacity. The soil samples were analyzed for particulate organic carbon (POC), and total and soluble carbohydrates (CHt and CHs, respectively). Oat and vetch residues decomposed faster than clover, with the decomposition rate constant (k) values of 1.3, 1.4 and 1.9 year-1, respectively. At the end of the experiment, POC concentration was lower in vetch (1.83 g kg-1) and clover (1.96 g kg-1) than in oat (2.21 g kg-1) and fallow (3.00 g kg-1), indicating a loss of 45-64% from their initial values. Soil CHt was influenced by residue quality, where the periods of greatest residue decay (vetch 21-59 days and oat 93-130 days) corresponded to higher soil CHt. Hence, this organic carbon fraction is sensitive to residue decomposition and can be indicators of changes in soil organic matter over short periods of time.